Valoração de efluentes de digestão de dejetos bovinos com cultivos mistos de microalgas - Magro, Francisco Gerhardt (2021)
The rapid development of cattle farming in a confined manner has produced a large amount of waste water, which can result in eutrophication of water bodies, contamination of groundwater. The cultivation of microalgae in effluents can contribute to the partial removal of nitrogen and phosphorus, helping in the treatment. In addition to the microalgae that assist in the treatment of the effluent, in several studies, they are considered promising and sustainable biomasses for the production of biofuels. Thus, the cultivation conditions in a consortium of microalgae Spirulina and Scenedesmus were studied. Initially, Zarrouk culture media diluted to 20%, BG-11 and modified BGZ medium cultivated with different microalgae in individual photobioreactors were studied. With the growth kinetics, it was observed that the microalgae cultivated with the Zarrouk medium 20% showed greater growth, as well as a greater accumulation of intracellular carbohydrates. Subsequently, laboratory-scale cultivation of the microalgae Spirulina platensis and Scenedesmus obliquus was carried out in consortia using effluents from the anaerobic treatment of bovine manure, in order to facilitate the production of microalgae biomass for use in biorefineries. The obtained biomasses were characterized to evaluate the potential for the production of biofuels and other bioproducts. The effluent was used in sterile and non-sterile conditions to better understand the influence of other microorganisms in the removal of N and P. The biomass obtained with the addition of 10% sterile effluent in Zarrouk medium (20%) presented 44.12% and 34.62% of carbohydrates, using Spirulina platensis in monoculture or the consortia 50% / 50% of Spirulina and Scenedesmus, respectively, this biomass presenting potential to be used in the production of bioethanol. The nitrogen and phosphorus removals were greater in non-sterile conditions and reached 92.7% and 49.66% nitrogen and phosphorus removal, respectively, using the consortia and with the addition of 30% of effluent in the medium. Finally, pilot scale cultivation was performed in 10 L raceways, the best result being replicated in a 100 L raceway. The tests were performed with the addition of non-sterile effluent, 10% (v / v) was added on days 1, 5 and 10, in the form of fed batch. The obtained biomasses were characterized to evaluate the potential for the production of biofuels and other bioproducts. The crops that reached the highest dry mass were 50% Sc + 50% Sp at 15 days of cultivation, and the highest concentration of carbohydrates was achieved at 100% Sp. There was a removal of 16.75% of phosphorus and 88.2% nitrogen in the first 5 days of cultivation. The scale increase (raceway 100L) showed similar results in comparison to the cultivation performed in the 10L raceways. The cultivation of microalgae in consortium or Spirulina in isolation can be used to assist the treatment of the effluent concomitantly with the production of biomass for different applications